2005
DOI: 10.1212/01.wnl.0000158281.08946.68
|View full text |Cite
|
Sign up to set email alerts
|

Serum inflammatory proteins and cognitive decline in older persons

Abstract: This population-based study showed that the serum inflammatory protein alpha1-antichymotrypsin is associated with cognitive decline in older persons, whereas C-reactive protein, interleukin-6, and albumin are not.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
230
3
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(245 citation statements)
references
References 35 publications
8
230
3
4
Order By: Relevance
“…Our finding that CRP is lower among those with any APOE4 is consistent with most reports for other populations. Another published study in a population-based study of the association between dementia incidence and CRP [Dik, Jonker, et al 2005 ], found no association between CRP and dementia but, in a recent analysis of three CRP genotypes [van Oijen, de Maat, et al 2006 ] the authors found one haplotype that was associated with increased rate of dementia. This was not evaluated in relation to APOE.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Our finding that CRP is lower among those with any APOE4 is consistent with most reports for other populations. Another published study in a population-based study of the association between dementia incidence and CRP [Dik, Jonker, et al 2005 ], found no association between CRP and dementia but, in a recent analysis of three CRP genotypes [van Oijen, de Maat, et al 2006 ] the authors found one haplotype that was associated with increased rate of dementia. This was not evaluated in relation to APOE.…”
Section: Discussionmentioning
confidence: 95%
“…This was not evaluated in relation to APOE. Other research relating CRP to cognition [Kuo, Yen, et al 2005 ] [Yaffe, Lindquist, et al 2003 ] [Dik, Jonker, et al 2005 ] [Tilvis, Kahonen-Vare, et al 2004 ] [Yaffe, Lindquist, et al 2003 ] has produced conflicting results. Elevated CRP has been linked to cardiovascular disease, atherosclerosis and ischemic stroke [Ridker, Haughie 1998 ] [Kuo, Yen, et al 2005 ] [van Dijk, Prins, et al 2005 ] which are themselves associated with higher risk of cognitive impairments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two large population-based studies in older adults observed that participants with high IL-6 levels had higher rates of cognitive decline after 2.5, 3, and 7 years of follow-up, independent of race, other vascular risk factors, and Creactive protein levels (Economos et al 2013;Weaver et al 2002). However, no association for IL-6 levels and cognitive decline was reported in two other studies of middle-aged or older adults (Dik et al 2005;Gimeno et al 2008). However, these inconsistent associations could be because of age differences.…”
Section: Discussionmentioning
confidence: 97%
“…The relationship between immune markers, such as IL-1ÎČ, IL-6, IL-8, TNF-α, and CRP, and cognitive functioning has been described in several population studies on older persons (Singh and Newman 2011;Holmes et al 2003;Baune et al 2008;Weaver et al 2002;Bruunsgaard et al 1999;Dik et al 2005;van Exel et al 2003).…”
mentioning
confidence: 99%